2015
DOI: 10.1002/ana.24524
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance neurography detects diabetic neuropathy early and with Proximal Predominance

Abstract: ObjectiveThe aim of this work was to localize and quantify alterations of nerve microstructure in diabetic polyneuropathy (DPN) by magnetic resonance (MR) neurography with large anatomical coverage.MethodsPatients (N = 25) with mild‐to‐moderate (Neuropathy‐Symptom‐Score [NSS]/Neuropathy Deficit Score [NDS] 3.8 ± 0.3/2.6 ± 0.5) and patients (n = 10) with severe DPN (6.2 ± 0.6/7.4 ± 0.5) were compared to patients (n = 15) with diabetes but no DPN and to age‐/sex‐matched nondiabetic controls (n = 25). All subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
102
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 92 publications
(121 citation statements)
references
References 32 publications
10
102
1
3
Order By: Relevance
“…3032 Recent neuroimaging studies of diabetic and neurofibromatosis-associated polyneuropathies have shown the disseminated multifocality of nerve lesions whose cumulation correlates with symptom severity. 33,34 A length-dependent radial mononeuropathy could first present with finger drop, as seen in our patients, before eventually proceeding to involve additional muscles. This was actually the case in 4 patients excluded from our study because their disease had progressed before the MRI to also involve more proximal muscles.…”
Section: Discussionsupporting
confidence: 63%
“…3032 Recent neuroimaging studies of diabetic and neurofibromatosis-associated polyneuropathies have shown the disseminated multifocality of nerve lesions whose cumulation correlates with symptom severity. 33,34 A length-dependent radial mononeuropathy could first present with finger drop, as seen in our patients, before eventually proceeding to involve additional muscles. This was actually the case in 4 patients excluded from our study because their disease had progressed before the MRI to also involve more proximal muscles.…”
Section: Discussionsupporting
confidence: 63%
“…All participants were examined feet first, in supine position in a 3.0 Tesla MR scanner (Magnetom TIM‐TRIO, Siemens Healthineers, Erlangen, Germany), and a 15‐channel Transmit‐Receive knee‐coil (INVIVO, Gainesville, FL, USA) was positioned at the right distal thigh. The thigh was chosen as previous studies showed a strong predominance of nerve lesions at this anatomical location not only in ATTRv‐PNP but also in other PNPs 15,17,18 . Two axial three‐dimensional, gradient echo sequences with and without an off‐resonance saturation pulse (Gaussian envelop, duration = 9984 µsec, frequency offset = 1200 Hz) were carried out at the exact same slice position and with the following exact same sequence parameters:…”
Section: Methodsmentioning
confidence: 99%
“…MR neurography (MRN) can overcome some of the aforementioned diagnostic limitations by directly visualizing peripheral nerve lesions 11–21 . The quantitative MRN parameters, proton spin density ( ρ ) and apparent T2 relaxation time ( T2 app ), have previously proven their feasibility to detect subclinical and early nerve lesions as well as to differentiate between neuropathic patients and controls or even between different disease severities in several neuropathies 14–18 . However, the changes in macromolecular structures that underlie alterations in ρ and T2 app still need to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, MRN can play a key role in understanding the spatiotemporal distribution and propagation of microstructural nerve alterations in DPN and for early monitoring of microstructural effects of therapeutic interventions. 134 More recently, several variations of MRN sequences have been proposed, which can achieve both high resolution and good fat suppression on 3T scanners. 135 …”
Section: Non-invasive Mri Techniques To Assess Dpn Featuresmentioning
confidence: 99%